Competition Law and the Investment Climate in Developing Countries - Evenett, Simon (Washington, DC: World Bank, 2012)
Nearly 100 countries have enacted competition laws, and there is a growing record of enforcement actions by competition agencies in developing countries. The econometric literature on the effects of competition law on investment in these countries focuses almost exclusively on the consequences for inflows of foreign direct investment. Equally as important though less studied is the potential effects of competition law enforcement on the level and composition of investment by state bodies and by domestic firms. Even though investment can play an important role in promoting development, the overarching goal of competition law and enforcement should be to promote static and dynamic efficiency and contribute substantially to improving the allocation of resources in the economy.